ANALYSIS OF THE CHIRPLET TRANSFORM-BASED ALGORITHM FOR RADAR DETECTION OF ACCELERATED TARGETS - V. G. Galushko; D. M. Vavriv (Radio Physics and Radio Astronomy, 2017)
Purpose: Efficiency analysis of an optimal algorithm of chirp signal processing based on the chirplet transform as applied to detection of radar targets in uniformly accelerated motion.